Information Culture And Business Performance In The Ghanaian Banking Industry - Mottey, E. (University Of Ghana, 2021)
This study examines the effect of information culture on business performance in the Ghanaian banking industry. Using purposive and convenience sampling techniques in a quantitative survey, 158 participants from a total population of 316 were sampled from a foreign and a local bank who responded to the questionnaire. The Statistical Package for Social Scientists (SPSS) version 22 was used to analyze data. Findings indicate that, information culture has positive effects on business performance of the banks. The most dominant information culture of each bank is integrity culture, with the least dominant cultures of the local and foreign banks being control culture and formality culture respectively. Both foreign and local banks had some form of support to promote information behaviours, however evaluation and reward systems were lacking. The foreign bank employed mechanisms to avoid information overload whereas the local bank did not. Furthermore, there were mechanisms and policies to manage information in both foreign and local banks but its implementation was not effective. The major challenges identified in both banks include, the lack of training for staff on the information policy available and the absence of a collective responsibility towards the effective management of information. The study recommends that, management of banks regularly train staff on effective information management and information management professionals must receive support in the form of participation and co-operation from all staff. Further research on information culture could focus on sectors like health, education, insurance, security and government ministries and departments using qualitative or mixed methods.
MPhil. Information Studies
Keywords: Ghanaian; Banking Industry; Information Culture; Business Performance